2021
DOI: 10.1016/j.cca.2021.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response induced by the boost overdose during COVID-19 heterologous prime-boost vaccination strategy

Abstract: Background Measurement of anti-SARS-CoV-2 RBD Ig G antibody response is very important to define the dynamics of immunization in vaccine COVID-19 recipients. Materials and methods Sera from four BNT162b2 vaccine recipients who erroneously received vaccine overdose were analyzed at different time-points. Results At 6 days the serum increase of antibodies was analogous for the three SARS-CoV-2 naïve recipients. At 14 days the antibody level inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The total seropositivity rate of serum IgM and IgG antibodies in August in the present study population was higher than that in February and March, and the serum IgG and IgM antibody levels gradually decreased over time in September and October. This decline suggested that the IgG antibody could not maintain at a higher level for a longer time in the body, and it is necessary to strengthen vaccination [6,23]. After beginning the booster vaccination at the end of October in Beijing, the IgG antibody seropositivity rate in November increased compared with that in September and October.…”
Section: Discussionmentioning
confidence: 99%
“…The total seropositivity rate of serum IgM and IgG antibodies in August in the present study population was higher than that in February and March, and the serum IgG and IgM antibody levels gradually decreased over time in September and October. This decline suggested that the IgG antibody could not maintain at a higher level for a longer time in the body, and it is necessary to strengthen vaccination [6,23]. After beginning the booster vaccination at the end of October in Beijing, the IgG antibody seropositivity rate in November increased compared with that in September and October.…”
Section: Discussionmentioning
confidence: 99%
“…Overdose with the BNT162b2 vaccine injections has been reported in Australia, Germany, Italy, and the United States. 6 In this study, we reported 25 recipients who erroneously received undiluted BNT162b2 vaccine and adverse events and laboratory abnormalities were prospectively monitered.…”
Section: Introductionmentioning
confidence: 99%
“…The currently available data suggest that the primary series of prime‐boost heterologous vaccination combination of AZ/PZ and rAd26/rAd5 (Sputnik) induce a strong and broad immune response in healthy individuals. 23 , 24 , 25 , 26 , 27 , 28 , 29 Immunogenicity data on other heterologous vaccination regimens (i.e., 2SV with AZ or PZ booster), however, are limited.…”
Section: Introductionmentioning
confidence: 99%